Comparative Analysis of Criminal Liability for Bribery in Lithuania and Poland - Levon, Justyna; Drakšas, Romualdas; Raglewski, Janusz (Teisė, 2026)
The article analyzes certain problematic aspects of bribery, as discussed by scientists in Poland and Lithuania. It should be noted that both countries face challenges in determining what constitutes personal benefit (lt. asmeninė nauda) when it comes to types of bribes. It is also worth noting that, in Polish criminal law science, the issue of distinguishing between a bribe and a gift receives considerable attention. The analysis is primarily focused on the professions of doctors and teachers. However, in the case of Lithuania, this issue seems to be somewhat less discussed.